Analisis Pengelolaan Data Keuangan Klien Menggunakan Microsoft Excel pada Kantor Konsultan Keuangan Artcounting - Seilaputri Sugini; Firman Yudhanegara (INDO PUBLISHING, 2026)
Accurate and systematic financial data management is a crucial aspect in supporting service quality at financial and accounting consulting firms. This study aims to analyze the management of client financial data using Microsoft Excel at a financial consulting firm. The research method used is a descriptive method with a qualitative approach through observation, documentation, and direct involvement during the Field Work Practice (PKL). The results show that Microsoft Excel is used in the process of entering, processing, and compiling client financial data, such as bank statements, financial transactions, and inventory data. The use of Microsoft Excel improves work efficiency, simplifies data management, and supports the accuracy and availability of financial information. Thus, Microsoft Excel plays a crucial role in supporting the effective management of client financial data at the Artcounting Financial Consulting Firm.